2022
DOI: 10.1021/acs.jpca.2c03828
|View full text |Cite
|
Sign up to set email alerts
|

Rate Coefficients for the Gas-Phase Reactions of Nitrate Radicals with a Series of Furan Compounds

Abstract: The atmospheric reaction of a series of furan compounds (furan (F), 2methylfuran (2-MF), 3-methylfuran (3-MF), 2,5-dimethylfuran (2,5-DMF), and 2,3,5trimethylfuran (2,3,5-TMF)) with nitrate radical (NO 3 ) has been investigated using the relative rate kinetic method in the CHamber for the Atmospheric Reactivity and the Metrology of the Environment (CHARME) simulation chamber at the laboratoire de Physico-Chimie de l'Atmosphere (LPCA) laboratory (Dunkerque, France). The experiments were performed at (294 ± 2) K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 45 publications
2
22
0
Order By: Relevance
“…The furan atmospheric lifetime due to OH reactive loss, τ(OH), using k from this work and a globally averaged OH concentration of 10 6 molecule cm −3 , was estimated to be 6.2 h. Newland et al 44 and Al Ali et al 45 have reported room temperature rate coefficients for the NO 3 radical + C 4 H 4 O reaction to be (1.49 ± 0.23) × 10 −12 and (1.51 ± 0.38) × 10 −12 cm 3 molecule −1 s −1 , respectively. They estimated daytime and nighttime furan lifetimes, τ(NO 3 ), of 19 and ∼1 h, respectively, for NO 3 reactive loss using 1 × 10 7 (daytime) and 2 × 10 8 (nighttime) molecule cm −3 NO 3 radical concentrations.…”
Section: Atmospheric Implicationsmentioning
confidence: 82%
See 1 more Smart Citation
“…The furan atmospheric lifetime due to OH reactive loss, τ(OH), using k from this work and a globally averaged OH concentration of 10 6 molecule cm −3 , was estimated to be 6.2 h. Newland et al 44 and Al Ali et al 45 have reported room temperature rate coefficients for the NO 3 radical + C 4 H 4 O reaction to be (1.49 ± 0.23) × 10 −12 and (1.51 ± 0.38) × 10 −12 cm 3 molecule −1 s −1 , respectively. They estimated daytime and nighttime furan lifetimes, τ(NO 3 ), of 19 and ∼1 h, respectively, for NO 3 reactive loss using 1 × 10 7 (daytime) and 2 × 10 8 (nighttime) molecule cm −3 NO 3 radical concentrations.…”
Section: Atmospheric Implicationsmentioning
confidence: 82%
“…Newland et al 44 . and Al Ali et al 45 . have reported room temperature rate coefficients for the NO 3 radical + C 4 H 4 O reaction to be (1.49 ± 0.23) × 10 −12 and (1.51 ± 0.38) × 10 −12 cm 3 molecule −1 s −1 , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The value reported in Atkinson et al 140 has been updated using the IUPAC recommended rate coefficient for the NO 3 + trans-2butene reaction. The rate coefficients of the reference molecules used in the studies of Kind et al, 141 Newland et al, 142 and Al Ali et al 143 are consistent with IUPAC recommendations and therefore have not been adjusted. The relative rate kinetic results agree to within 33% across all of these studies The rate constant reported by Kind et al 141 is lower than others, and when excluded, the remaining studies agree to within 5%.…”
Section: Tetrahydrofuran + Nomentioning
confidence: 95%
“…Each study determined rate coefficients using the relative rate method. Kind et al 141 used 2,3-dimethyl-2-butene as a reference molecule, Alvarado et al 144 used 2-methyl-2-butene and Tapia et al 125 used α-pinene, while Al Ali et al 143 used 2-methyl-2-butene, γ-terpinene, and αpinene. Kind et al 141 reported a rate coefficient that is independent of pressure between 5 and 150 Torr.…”
Section: -Methylfuran + Nomentioning
confidence: 99%
“…Plasma technology is an optimal method for surface modification that can be applied quickly and easily with fewer external physical and chemical influences than chemical methods or laser irradiation [19,20]. In this study, material surface modification was carried out through the gas-phase plasma process at atmospheric pressure, which has been used in various fields for a long time, and its safety and effectiveness have been verified [21][22][23].…”
Section: Introductionmentioning
confidence: 99%